Breast metastasis around dental implants: A case report - Dib, Luciano Lauria; Soares, Ana Laura; Sandoval, Renata Lazzari; Nannmark, Ulf (Blackwell Publishing, 2007)
Background: Metastases to the oral cavity and to the jaws are rare; hence, the clinical manifestations of the oral metastasis lesion could frequently be simulating general pathologic entities, making the diagnosis a challenging process to the dental team. Local factors, such as trauma, have been observed to facilitate the growth of blood-borne tumors. To this end, surgical procedures such as fixture placement might cause cancer cells to spread. Purpose: Careful clinical examination is a valuable help in diagnosing oral lesions, which can improve the quality of life of patients and reduce the risks of oral complications. Materials and Methods: A female patient was referred to the clinic with symptoms of irritation, swelling, and pain associated with implants in the mandible and the maxilla. Results: Clinical examination, x-ray, and histopathology revealed that the patients suffered from a metastatic lesion, primary tumor being an adenocarcinoma of the breast diagnosed at the same time. Conclusion: Optimal clinical examination in conjunction with radiography and histopathology is a necessity in order to discover malignant lesions in time. Routine dental check-ups must comprise more thorough soft-tissue examination.
Keywords: cancer metastasis; dental implants; oral rehabilitation; tumor spread